PENGARUH PEMEDIASIAN KEUNGGULAN BERSAING TERHADAP HUBUNGAN ORIENTASI KEWIRAUSAHAAN DENGAN KINERJA PERUSAHAAN: STUDI PADA UMKM - , Mulato Santosa, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to test the role of mediating variables competitive advantage on the relationship between entrepreneurial orientation and firm performance.This research was conducted by survey method by distributing questionnaires to the respondents are small and medium enterprise in Magelang City. The sample size of this study are 115 respondents. Data analysis was performed using SmartPLS 2.0 M3. The results show bahwa entrepeneurial orientation has direct relation and significan with firm performance (t-value=7,041, Ã=0,440). Than competitive advantage as mediator variable has significan relation with entrepreneurial orientation (t-value = 14.613, Ã=0,725) and has significan relation with firm performance (t-value = 8,698, Ã=0,608). Model has value GoF = 0,536 that indicated model has good GoF. The results of the research indicated that competitive advantage partially mediated the relationship of entrepreneurial orientation on firm performance.